2018
DOI: 10.1371/journal.pone.0199166
|View full text |Cite
|
Sign up to set email alerts
|

Second harmonic generation microscopy provides accurate automated staging of liver fibrosis in patients with non-alcoholic fatty liver disease

Abstract: BackgroundAssessment of severity of liver fibrosis is essential in the management of non-alcoholic fatty liver disease (NAFLD). Second Harmonic Generation (SHG) microscopy is a novel optical tissue imaging system that provides automated quantification of fibrosis based on unique architectural features of collagen. This study aims to develop and validate a SHG-based index for automated staging of liver fibrosis in patients with NAFLD.MethodsSHG microscopy was performed on archived liver biopsy specimens from 83… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 29 publications
0
38
1
Order By: Relevance
“…Automatic quantification of lobular inflammation and ballooning on digital images of H&E‐stained slides has also been reported: R values were 0.45 for lobular inflammation and 0.46 for ballooning, AUC values were 0.95 for lobular inflammation and 0.98 for ballooning . Others have demonstrated that LF could be quantified using a range of techniques, such as collagen proportionate area and dual‐photon microscopy, but these studies have tended to be in mixed etiology cohorts, or derived from single centers, and histological characteristics other than fibrosis were not assessed. In contrast, the current study derives NAFLD/NASH cases associated samples from a large international, multicenter collaboration and therefore provides an opportunity to not only comprehensively assess key histological features of NASH, but also to demonstrate utility across differing ethnicities, environmental/nutritional backgrounds, and age groups (adult and pediatric disease).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Automatic quantification of lobular inflammation and ballooning on digital images of H&E‐stained slides has also been reported: R values were 0.45 for lobular inflammation and 0.46 for ballooning, AUC values were 0.95 for lobular inflammation and 0.98 for ballooning . Others have demonstrated that LF could be quantified using a range of techniques, such as collagen proportionate area and dual‐photon microscopy, but these studies have tended to be in mixed etiology cohorts, or derived from single centers, and histological characteristics other than fibrosis were not assessed. In contrast, the current study derives NAFLD/NASH cases associated samples from a large international, multicenter collaboration and therefore provides an opportunity to not only comprehensively assess key histological features of NASH, but also to demonstrate utility across differing ethnicities, environmental/nutritional backgrounds, and age groups (adult and pediatric disease).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al first established an SHG‐based quantification of fibrosis‐related parameters (Q‐FP) model in NAFLD that offered a more refined assessment of collagen architectural changes along a continuous, quantitative scale. Liu et al and Chang et al subsequently described the use of SHG to autoquantify collagen deposition and assess fibrosis in pediatric and adult patients with NAFLD. To further explore the utility and potential of SHG in the context of NAFLD, we carried out an international, multicenter study to develop and validate a SHG‐based automated quantitative evaluation tool, qFIBS, for the evaluation of fibrosis as well as lobular inflammation, ballooning, and steatosis, with the goal of increasing the precision of disease severity assessment following the confirmation of an NAFLD/NASH diagnosis by expert hepatopathologist consensus .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…11 Furthermore, to our knowledge, very few studies have attempted a quantitative assessment of ballooning and inflammation in NAFLD. 12,13 A recent consensus document from the Case Definitions Working Group of the Liver Forum recognized the potential role of quantitation as an entry criterion to drug trials within the field. 14 This study's primary aim was to develop and validate a high-throughput, fully automated, machine learning-based system for the quantitation of all 4 key histologic features contributing to the NASH CRN score, using liver biopsy specimens obtained from patients with NAFLD.…”
Section: Q9mentioning
confidence: 99%
“…Note: To access the supplementary material accompanying this article, visit the online version of Clinical Gastroenterology and Hepatology at www.cghjournal.org, and at https://doi.org/10.1016/j.cgh.2019. 12…”
Section: Supplementary Materialsmentioning
confidence: 99%